The perception of managers in different business establishments in Iloilo City on Homosexuality - Fernandez, Pitchit; Libron, Aileen; Peñaflor, Reynon; Pornel, Ma. Rhoda
Executive summary - This is the research study that will eventually solicit the perceptions of managers in the different organizations in Iloilo City regarding how they view homosexuality, taken into general context. This study was conducted to determine the degree of probability that a homosexual applicant be hired in an organization. The aim of the researchers is also to seize the managerial position or any position that can be delegated to a gay employee by managers who view gender as determinant of job promotion. There are common notions about this sexual minorities and this will be presented as to the aspects that influences the opinion of the society. The conservativeness of the filipino culture is the major hindrance to the acceptance of gays in the society, specifically in the workplace. However, these prejudices have been superficial to the fact that gays now enjoy more rights and privileges, even though in a very limited sense. The grand march for gay liberalism, is in sense, has garnered deeper roots. The study is to prove that homosexuals are seen with much ease at workplace, but somehow constrained to much demeaning roles in organization. The struggle for equality is a long and tedious path, and it is the cry of the homosexuals in the workplace.